The correlation between social media use, peer influence, and sexual behaviour among adolescents - Hastutii, Puji; Salsabila, Ramadhanti; Budiarti, Astrida; Yunitasari, Esti (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the correlation among social media use, peer influence and sexual risk behaviour among school going adolescents. Method: The cross-sectional study was conducted from April to July 2022 after approval from the ethics review board of Stikes, Hang Tuah, Surabaya, Indonesia, and comprised grade 11 students of either gender at the Senior High School 1, Hang Tuah, Surabaya. Data was collected using social media and peer influence questionnaires. Data was analysed using SPSS version 23. Results: Of the 134 participants, 79(59%) were males, and 91(67.9%) were aged 17 years. Highly frequent social media usage was reported by 81(60.4%) subjects, getting influenced by peers by 82(61.2%) and sexual risk behaviour by 88(65.7%). Social media usage and peer influence were significantly associated with sexual behaviour (p<0.05). Conclusion: A significant relationship was noted of sexual behaviour with social media usage and peer influence. Keywords: Sexual behaviour, Adolescent, Demography, Social media, Peer influence.